At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

The value of the expression [tex]\frac{2x^2}{x} + x(100 - 15x)[/tex] when [tex]x = 5[/tex] is

A. 119
B. 129
C. 135
D. 145


Sagot :

To find the value of the expression [tex]\(\frac{2 x^2}{x} + x(100 - 15x)\)[/tex] when [tex]\(x = 5\)[/tex], we will evaluate each term in the expression step-by-step.

1. Start by substituting [tex]\(x = 5\)[/tex] into the first term:
[tex]\[ \frac{2 x^2}{x} \][/tex]
Replacing [tex]\(x\)[/tex] with 5:
[tex]\[ \frac{2 \cdot 5^2}{5} \][/tex]
Calculate [tex]\(5^2\)[/tex]:
[tex]\[ 5^2 = 25 \][/tex]
Now, multiply by 2:
[tex]\[ 2 \cdot 25 = 50 \][/tex]
Finally, divide by 5:
[tex]\[ \frac{50}{5} = 10 \][/tex]
So, the first term when [tex]\(x = 5\)[/tex] is 10.

2. Next, substitute [tex]\(x = 5\)[/tex] into the second term:
[tex]\[ x(100 - 15x) \][/tex]
Replacing [tex]\(x\)[/tex] with 5:
[tex]\[ 5(100 - 15 \cdot 5) \][/tex]
First, calculate the multiplication inside the parentheses:
[tex]\[ 15 \cdot 5 = 75 \][/tex]
Now, subtract from 100:
[tex]\[ 100 - 75 = 25 \][/tex]
Finally, multiply by 5:
[tex]\[ 5 \cdot 25 = 125 \][/tex]
So, the second term when [tex]\(x = 5\)[/tex] is 125.

3. To find the total value of the expression, sum the first and second terms:
[tex]\[ 10 + 125 \][/tex]
This gives:
[tex]\[ 10 + 125 = 135 \][/tex]

Therefore, the value of the expression [tex]\(\frac{2 x^2}{x} + x(100 - 15x)\)[/tex] when [tex]\(x = 5\)[/tex] is [tex]\(\boxed{135}\)[/tex].